The Association Between Periodontitis, Gingivitis, Tooth Loss and Stroke: An Umbrella Study with Meta-Analysis - Jad El Masri; Ahmad Al Malak; Diala El Masri; Maya Ghazi; Silva Al Boussi; Yasmina El Masri; Mohammad Hassoun; Maryam Tlayss; Pascale Salameh; Hassan Hosseini (Brain Sciences, 2024)
Background: Cerebrovascular diseases (CVAs) have several risk factors that are categorized as modifiable and nonmodifiable. Periodontal diseases (PD) have a modifiable role in causing CVA, where several studies suggested direct or indirect correlations with systemic diseases. This study aims to summarize, evaluate and analyze all the evidence available in literature, to reach a better understanding of the relation between periodontitis, gingivitis, tooth loss and CVA. Methods: PubMed, Cochrane, Scopus and Web of Science databases were searched for all meta-analyses assessing the effect of PD on CVA in accordance with Joanna Briggs Institute guidance for umbrella reviews in March 2024. Assessment of Multiple Systematic Reviews (AMSTAR) was used for quality assessment. Pooled analysis was performed to assess the effect of periodontitis, gingivitis and tooth loss on CVA, depending on the availability of data using Review Manager Version 5.2.11. Results: Seven of the identified meta-analyses were of high quality, and they were distributed in different countries. Periodontitis was generally associated with a significant increase in CVA risk (OR = 2.32, 95% CI: 1.70, 3.17, p < 0.00001 and RR = 1.22, 95% CI: 1.15–1.29, p < 0.00001), same as tooth loss, but to a lower degree (0.78). However, the effect of gingivitis was insignificant in terms of CVA (RR = 1.32, 95% CI: 1.12–1.56, p = 0.0008). Conclusions: This study confirms the effect of periodontitis and tooth loss on CVA, disregarding any significant role for gingivitis. The relation reached favors the suggested role of some inflammatory changes in the pathogenic pathway leading to atherosclerotic changes.